COATING OF CHITOSAN AND SALICYLIC ACID CAN MAINTAIN QUALITY CHARACTERISTICS OF TABLE GRAPES - Mustafa OZDEN; Rohullah Qaderi (Journal of Animal and Plant Sciences, 2023)
International fresh table grape trade has expanded tremendously over the last few decades. However, fresh table grapes decay quickly due to pathogen infestation and water loss, which make it difficult to preserve without an effective treatment. Therefore, this study was conducted to investigate the effects of CT, with SA on maintaining quality characteristics of ‘Red Globe’ grapes during storage at 0.5°C and 90-95% RH in pomology laboratories of the faculty in 2018-2019. The experiment was conducted using a completely randomized design with treatments [1% CT and two concentrations of SA (0, 1 and 2 mM)] fora 60 day of storage time. To determine the effects of the treatmentsat 15-day intervals, weight loss, fruit decay, chroma index, total soluble solids, titratable acidity (TA), pH, fruit flesh firmness and secondary metabolites such as total phenolic contents, total flavonoids and total anthocyanins were determined. Also, antioxidant activity and antioxidant capacity of the berry extracts determined by the DPPH and FRAP assays at each sampling time. Results revealed no effect on total soluble solids and total phenolics However, there were significant effects on the quality parameters fruit decay, weight loss, TA, pH, chroma index, and fruit flesh firmness. Chitosan coating was also found to be a potentially useful treatment for the phytochemical compounds and total antioxidant activity. The pre-storage IC50 value of the berry extract was 0.53 mg mL-1 and by the end of storage period, the values were 0.49 mg mL-1 in control, 0.50 mg mL-1 in CT, 0.53 mg mL-1 in CT + 1 mM SA and 0.46 mg mL-1 in CT + 2 mM SA. Total antioxidant capacity of grapes was 23.7 mg BHT mL-1 before storage and this increased during storage for both coated and uncoated grapes. Based on the findings, there was a strong relationship between total phenolic and flavonoid contents of the berries and antioxidant activity. It was concluded that the use of CT + 2 mM SA together with MAP is a potentially useful alternative to the use of SO2 in grape storage in commercial contexts.
Keywords: cold storage; chitosan; coating; salicylic acid; Vitisvinifera